EFFECT OF FEEDING WITH DIFFERENT NITROGEN FERTILIZERS ON 1000-GRAIN WEIGHT OF WINTER WHEAT (British Journal of Global Ecology and Sustainable Development, 2026)
This article analyzes the effect of various forms and application rates of nitrogen fertilizers on the technological indicators of winter wheat grain, in particular, on the weight of 1000 grains. During the study, 15 different fertilization systems were compared, and the highest efficiency was found in the variant (N240) using urea in spring collection and ammonium nitrate in tube feeding. The results obtained serve to increase the efficiency of the use of mineral fertilizers in grain production.